2016
DOI: 10.1515/cpe-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Mass flow and particle size monitoring of pulverised fuel vertical spindle mills

Abstract: The first step towards condition based maintenance of the milling plant is the implementation of online condition monitoring of the mill. The following paper presents and analyses methods of monitoring the key performance factors of a vertical spindle mill that is suited for implementation on older power stations, i.e. the quantity (mass flow rate) and quality (particle fineness) of the pulverised fuel produced by the mill. It is shown herein that the mill throughput can be monitored on-line using a simple mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The isokinetic sampling method could also explain these differences. Archary et al [55] found that sampling coal at the center of vertically oriented burner pipes resulted in a higher concentration of coarse comminuted particles, while the fine particle fraction moved near the pipe wall. Hence, a coarser PSD of the comminuted I2 pellets may lead to an even higher concentration of coarser particles at the inner part of the pipe that is collected by the isokinetic sampling device.…”
Section: Milling Behavior Of I1 and I2 Pelletsmentioning
confidence: 99%
“…The isokinetic sampling method could also explain these differences. Archary et al [55] found that sampling coal at the center of vertically oriented burner pipes resulted in a higher concentration of coarse comminuted particles, while the fine particle fraction moved near the pipe wall. Hence, a coarser PSD of the comminuted I2 pellets may lead to an even higher concentration of coarser particles at the inner part of the pipe that is collected by the isokinetic sampling device.…”
Section: Milling Behavior Of I1 and I2 Pelletsmentioning
confidence: 99%